Um Teatro Com Consciencia De Classe: Produção Estético-Política Dos Grupos Ói Nóis Aqui Traveiz E Engenho Teatral - Sousa, Renata Adriana De [UNIFESP] (2018)
The Present Work Analyzes The Production Logic Of The Theater Groups Oi Nóis Aqui Traveiz, From Porto Alegre (Rs) And Engenho Theatrical, From São Paulo (Sp), Seeking To Establish The Relation Between Artistic Work, Production Mode And Political Action As A Whole Of Today's Political Theater. And In Such A Way, It Is Sought To Situate The Nexus Of This Artistic Performance As Coming From The Class Consciousness In The Contemporary Theater. Thus, We Treat The Problematic Of The Political Theater Through The Set Of Social Relations That Understands It, Starting From The Artistic Productions Of The Groups. In The Following Discussion We Articulate The Theoretical Debate In Which These Groups Are Involved In Relation To Aesthetic, Historical And Sociological Thought Combined With The Historical And Social Description Of The Groups Investigated. Based On The Assumption That They Are Groups That Propose To Act Through The Theater With Political Positioning For And For The Working Class, We Analyze The Social Determ